2014
DOI: 10.1097/ta.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid corrects fibrinolysis in the presence of acidemia in a swine model of severe ischemic reperfusion

Abstract: TXA rapidly and fully reverses hyperfibrinolysis despite severe acidemia in a porcine trauma model. TXA is a promising adjunct to trauma resuscitation that is easily administered in austere or prehospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…16 The ability of TXA to inhibit tPA-induced fibrinolysis had been demonstrated previously in an acidotic, coagulopathic swine model. 17 They used human recombinant tPA and injected it intravenously into their hemorrhaged, acidotic swine model to induce a transient fibrinolysis. We confirmed that human tPA does induce fibrinolysis in swine plasma, but we found that swine were 30-fold less sensitive to human rtPA and porcine tPA, although it should be noted that we did not use the same brand of human rtPA as that used by DeBarros et al 17 Interestingly, human plasma was affected equally by both human and swine tPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The ability of TXA to inhibit tPA-induced fibrinolysis had been demonstrated previously in an acidotic, coagulopathic swine model. 17 They used human recombinant tPA and injected it intravenously into their hemorrhaged, acidotic swine model to induce a transient fibrinolysis. We confirmed that human tPA does induce fibrinolysis in swine plasma, but we found that swine were 30-fold less sensitive to human rtPA and porcine tPA, although it should be noted that we did not use the same brand of human rtPA as that used by DeBarros et al 17 Interestingly, human plasma was affected equally by both human and swine tPA.…”
Section: Discussionmentioning
confidence: 99%
“…17 They used human recombinant tPA and injected it intravenously into their hemorrhaged, acidotic swine model to induce a transient fibrinolysis. We confirmed that human tPA does induce fibrinolysis in swine plasma, but we found that swine were 30-fold less sensitive to human rtPA and porcine tPA, although it should be noted that we did not use the same brand of human rtPA as that used by DeBarros et al 17 Interestingly, human plasma was affected equally by both human and swine tPA. Therefore, swine show more species specificity than the human in the response to tPA-induced fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of effective and easy to administer therapeutic interventions targeting hyperfibrinolysis and subsequent TIC in severe trauma patients is a high priority. The Food and Drug Administration–approved antifibrinolytic tranexamic acid (TXA) is a synthetic lysine analog that inhibits plasminogen activation, thereby leading to decreased clot lysis 11,12 . Current Tactical Combat Casualty Care and Military Clinical Practice Guidelines, as well as civilian trauma centers, recommend intravenous (IV) TXA administration within 3 hours of severe traumatic injury 13,14 .…”
mentioning
confidence: 99%
“…The Food and Drug Administration-approved antifibrinolytic tranexamic acid (TXA) is a synthetic lysine analog that inhibits plasminogen activation, thereby leading to decreased clot lysis. 11,12 Current Tactical Combat Casualty Care and Military Clinical Practice Guidelines, as well as civilian trauma centers, recommend intravenous (IV) TXA administration within 3 hours of severe traumatic injury. 13,14 Its use has been shown to reduce mortality when given within these first 3 hours.…”
mentioning
confidence: 99%